Semantic Field of Anger in L.N. Tolstoy’s “Father Sergius” Novel - Hovhannesyan, Gayane (Bulletin of Yerevan University H: Russian Philology, 2024)
The work examines L.N. Tolstoy’s story “Father Sergius” and the theme of anger/hot temper expressed in it. We consider the linguistic description of the topic within the framework of the concept of semantic field. Within a work of art, the semantic field shows a tendency towards expansion and contextual conditioning. Turning to the experience of scientists who have previously studied similar topics, we borrow from them the concept of a textual semantic field, which can be used as a tool for our work. We see that the semantic field as a linguistic category is capable of transformation in the text and provides material for new observation. The semantic field in a literary text goes beyond the use of its usual tools (synonymy, derivation) and acquires the transformational potential inherent in speech organics. This is the first we can see in the expansion of the field boundaries. Expansion occurs due to lexical content (unexpected to continue the field of lexemes), but also the semantic expression finds its manifestation in syntax through the techniques of tempo, intensification (frequency of use, repetition), compatibility. Anger is an important description trait of a personage. It is present in the overwhelming majority of the text. We see opportunities for highlighting this topic and considering it both in terms of filling the text (semantics, meaning, subtext, metaphors) and in terms of expression (external features of the text), which is supported by calculations and quantitative comparison. This theme coexists and intersects with other themes in the story and together creates a rich, tragically described image of human fate.
Keywords: “Father Sergius”; semantic field; anger; text semantic field; context; humility; exclusivity; vocabulary; synthesis